Subunit Vaccines Against Emerging Pathogenic Human Coronaviruses - Wang, Ning; Shang, Jian; Jiang, Shibo; Du, Lanying (Frontiers in Microbiology, 2020)
Seven coronaviruses (CoVs) have been isolated from humans so far. Among them, three emerging pathogenic CoVs, including severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV), and a newly identified CoV (2019-nCoV), once caused or continue to cause severe infections in humans, posing significant threats to global public health. SARS-CoV infection in humans (with about 10% case fatality rate) was first reported from China in 2002, while MERS-CoV infection in humans (with about 34.4% case fatality rate) was first reported from Saudi Arabia in June 2012. 2019-nCoV was first reported from China in December 2019, and is currently infecting more than twenty thousand people (with about 2.1% case fatality rate). Both SARS-CoV and MERS-CoV are zoonotic viruses, using bats as their natural reservoirs, and then transmitting through intermediate hosts, leading to human infections. Nevertheless, the intermediate host for 2019-nCoV is still under investigation and the vaccines against this new CoV have not been available. Although a variety of vaccines have been developed against infections of SARS-CoV and MERS-CoV, none of them has been approved for use in humans. In this review, we have described the structure and function of key proteins of emerging human CoVs, overviewed the current vaccine types to be developed against SARS-CoV and MERS-CoV, and summarized recent advances in subunit vaccines against these two pathogenic human CoVs. These subunit vaccines are introduced on the basis of full-length spike (S) protein, receptor-binding domain (RBD), non-RBD S protein fragments, and non-S structural proteins, and the potential factors affecting these subunit vaccines are also illustrated. Overall, this review will be helpful for rapid design and development of vaccines against the new 2019-nCoV and any future CoVs with pandemic potential. This review was written for the topic of Antivirals for Emerging Viruses: Vaccines and Therapeutics in the Virology section of Frontiers in Microbiology.